Predictive factors associated with sexual activity and consistent condom use during travel abroad: a cross-sectional survey of young Canadian adults - Gareau, Emmanuelle; Phillips, Karen P. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background For young adults seeking new experiences, international travel provides opportunities for casual sexual encounters. The aim of this study was to identify the predictive factors associated with travel-associated sex and consistent condom use in a non-random sample of single and partnered young travelers. Methods Sexually-active Canadians, aged 18–25 years, who traveled abroad in 2016, were purposively recruited to participate in an online survey. Two binomial logistic regressions were performed to examine the demographic, sexual health and lifestyle factors associated with (1) having sex abroad (N = 646), or (2) consistent external condom use abroad (n = 271 sexually-active travelers). Results Packing condoms for international travel was associated with more than twice the odds of both having sex abroad (AOR: 2.58, 95% CI: 1.47–4.51 p < 0.001) and using condoms consistently during intercourse (AOR: 2.62, 95% CI: 1.62–5.32, p = 0.008). Sex under the influence of alcohol at-home, history of sexually transmitted infections, travel-related plans to have sex and drug consumption were also associated with sex abroad. Consistent external condom use abroad was associated with prior condom use at-home and penetrative sexual practices abroad. Unlike previous studies, gender, sexual orientation and relationship status were not significantly associated with either travel-associated sex nor condom use. Conclusion Travelers’ characteristics and domestic sexual behaviors will inform travel health interventions, but our findings support universal promotion of barrier protection during travel regardless of relationship status, sexual orientation or gender identity. Given the increasingly open and fluid nature of sexual expressions and relationships, pre-travel sexual health interventions should be sex-positive, broadly inclusive and promote strategies for safe sexual behaviors while travelling.

Plain English summary The experience of international travel is often accompanied by risky behaviors including substance use and casual sex. Packing condoms for international travel was associated with a higher likelihood of travel-related sexual activity and consistent condom use. Behaviors at home including sex under the influence of alcohol, and history of sexually transmitted infections, were also linked with travel-related sex, whereas domestic condom use was associated with consistent condom use abroad. These factors can be incorporated in sex-positive, travel-sexual health promotion to ensure safe and responsible sexual activity abroad.